Comparative field performance of mature Japanese persimmon [Diospyros kaki] trees grafted on seedling rootstocks vs. micropropagated ones - Tetsumura, T. (Kyoto Univ. (Japan)); Koyanagi, Y; Ito, S; Habu, T; Kawase, K (Engei Gakkai zasshi, 2004)
The growth of micropropagated (M) Japanese persimmon (Diospyros kakl Thunb. cv. Nishimura wase) trees from the 8th to llth year after planting was compared with that of trees grafted on seedlings (G) in the orchard. The M trees grew more vigorously than did the G trees; the differences in tree canopy and trunk cross-sectional area between the M and G trees increased annually. The percentage of shoots with male flowers in the total number of shoots in the M trees was lower than that in the G trees., although the difference was not significant. The percentage of shoots with female flowers in the total number of shoots in the M trees was the same as that in the G trees. Although the yield per tree of M trees was larger than that of G trees, there was no significant difference between the G and M trees in the yield efficiency (yield per canopy volume). These results suggest that micropropagation caused reinvigoration, but not true rejuvenation. M trees showed uniform growth, flowering and fruiting.